Particle Velocity and Acceleration in Turbulent Bent Pipe Flows - Noorani, Azad; Sardina, Gaetano; Brandt, Luca; Schlatter, Philipp (Flow Turbulence and Combustion, 2015)
We study the dynamics of dilute micro-size inertial particles in turbulent curved pipe flows of different curvature by means of direct numerical simulations with one-way coupled Lagrangian particle tracking. The focus of this work is on the first and second order moments of the velocity and acceleration of the particulate phase, relevant statistics for any modelling effort, whereas the particle distribution is analysed in a previous companion paper. The aim is to understand the role of the cross-stream secondary motions (Dean vortices) on the particle dynamics. We identify the mean Dean vortices associated to the motion of the particles and show that these are moved towards the side-walls and, interestingly, more intense than those of the mean flow. Analysis of the streamwise particle flux reveals a substantial increase due to the secondary motions that brings particles towards the pipe core while moving them towards the outer bend. The in-plane particle flux, most intense in the flow viscous sub-layer along the side walls, increases with particle inertia and pipe curvature. The particle reflections at the outer bend, previously observed also in other strongly curved configurations, locally alter the particle axial and wall-normal velocity and increase turbulent kinetic energy.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Bent pipe; Curvature effect; Gas-solid flow; Particle transport; Particulate dispersion; Secondary motion